(untitled) (Collection of scientific works «Modern structures of metal and wood», 2020)
Analysis of the damage responsible for the vital activity of a span reinforced concrete structure, structure or building, in general, showed that during their operation there is a significant destruction of the concrete protective layer, corrosion of the reinforcement, crack formation and excessive opening, achievement of unacceptable deflections, etc. The aim of this work is to experimentally and theoretically study physical models reinforced with prestressed metal jackets damaged by through normal and transverse-inclined cracks in reinforced concrete beams under active low-cycle alternating loads of high levels. To this end, a method was created for the restoration of damaged reinforced concrete beams needed in an anticipated state, as a result of which alternating cyclic or pulsating loads of high levels arise, and a device for providing it. All tested beam samples were manufactured and tested in accordance with the experimental design theory and D-optimum plan of Box B4. The accomplished system approach to the experimental and theoretical research of the stress- strain behaviour of the common, renewed and strengthened reinforced concrete span structures damaged with through forced cracks with the aid of metal prestressed metal casings enabled to make a reliable quantitative and qualitative evaluation of the design factors and external factors impact on their load-bearing capacity, stiffness, crack resistance and other performance parameters, either individually or in their interaction with each other, considerably specify the physical model of said structures performance when subjected to static and low-cycle alternate loading. The experiments have proved a possibility and expediency of practical application of the ingenious method developed by the authors which is distinctive of renewal and strengthening of the damaged reinforced concrete beam structures damaged with through normal and cross inclined cracks which divide the beam into separate blocks due to three-side clamping, and the arrangement for its accomplishment claimed by the patent of invention subjected to action of the increasing static, cyclic, alternate, seismic, fluctuating and other dynamic loading, including, among other things, the reinforced concrete beams damaged during military activity provide such beams did not collapse completely and preserve their initial shape.